Reduction of Ascaridia galli Pathology by Salmonella typhimurium in Broiler Chicken - Eric Igor Sop Foka; Cedric Yamssi; Ben Enyetornye; Christelle Noumedem Anangmo; Mpoame Mbida; Theodore B. Mayaka (Journal of Parasitology Research)
Previous studies have reported interactions between Salmonella spp. and some helminth coinfections. In this study, S. typhimurium and Ascaridia galli coinfections were analyzed, and the consequences on therapy were proposed. In a first experiment where the effect of the bacteria on the nematode was evaluated, thirty 42-day-old broiler chickens were divided into 3 groups and coinfected with both parasites. The rate of A. galli egg inoculum was kept constant at 500/ml while that of S. typhimurium varied as follows: T0 (500 A. galli eggs/ml), T104 (500 A. galli eggs/ml+104 S. typhimurium CFUs), and T106 (500 A. galli eggs/ml +106S. typhymurium CFUs). EPG and parasitic load were measured using the McMaster technic, and number of worms and their length were also measured. We observed that T106 containing 106 CFUs of Salmonella significantly reduced the EPG values, and this group recorded the lowest worm load ranging from 18 to 21 worms. Likewise, the length of the worms obtained with T104 and T106 appeared to be shorter than those of the control (T0). In a second experiment to assess the effects of the nematode on the bacteria, thirty 42-day-old broiler chickens were divided into 3 groups and coinfected with both parasites. The rate of S. typhimurium inoculum was kept constant at 106 CFUs while that of A. galli varied as follows: T0 (106CFUs), T500 (500 A. galli eggs/ml +106S. typhymurium CFUs), and T750 (750 A. galli eggs/ml +106S. typhymurium CFUs). Bacterial load was measured using Voogt technique. We observed that T500 increased the colonization time and prolonged the duration of S. typhimurium secretion. Salmonella appears to be a hyperparasite considering the deleterious effect on A. galli. Due to this, it may be prudent to combine anti-Salmonella treatment with anthelmintic so as to effectively treat pathologies caused by these two pathogens.